(untitled) (Market-Tržište, 2025)
Purpose – This research study examines the impact of atmospheric cues, such as content, design, and navigation, on impulsive buying behavior, focusing on the mediating roles of utilitarian and hedonic browsing. Design/Methodology/Approach – The study utilized a quantitative method approach, employing SPSS and AMOS for data analysis. The convenience sampling method was used to select 363 participants as the target population, consisting of individuals 18-65 years old living in Turkey who had experience using two prominent e-store platforms. Data analysis was conducted using both descriptive and inferential statistics to describe the demographic profile and structural equation modelling (SEM) to examine the causal relationships between variables. Findings and Implications – Results showed that design and navigation features positively influence impulsive buying, but they did not significantly impact utilitarian behavior. Atmospheric features affected impulsive buying directly and indirectly. Content cues positively influenced utilitarian browsing but did not significantly affect hedonic browsing. Hedonic browsing mediated the relationship between design and navigation cues and impulsive buying. These findings suggest that e-store platforms should strategically design e-stores with visually appealing designs, including vibrant colors, attractive images, and easy navigation to promote both hedonic browsing and attract impulsive purchases. To encourage more shopping time, e-store managers should also focus on navigation and personalized recommendations while avoiding overwhelming customers with excessive information. Limitation – The study’s limitations include reliance on self-reported data, which may be subject to bias, and the use of a convenience sample that may not fully represent the diversity of online shoppers. Further research should employ longitudinal studies and a broader demographic to validate these findings further. Originality – This research study contributes to literature by integrating the concepts of atmospheric cues, hedonistic and utilitarian browsing, and their combined effects on online impulsive buying behavior. It offers a nuanced understanding of how different browsing motivations mediate the impact of online atmospherics on consumer behavior, providing practical insights for e-store design strategies.